Factores de riesgo asociados a enfermedad vascular cerebral en pacientes adultos en hospitales minsa de trujillo, 2014-2015 - Cortegana Aranda, José Alberto (2017)
Objective: Identify risk factors associated with Cerebral Vascular Disease in adult patients in hospitals MINSA CATEGORY III-1 of Trujillo during the period 2014-2015. Material and method: The study population was composed of 184 adult patients in the Hospital Belen and Hospital Regional of Trujillo, during the period 2014 - 2015. The group of cases and controls were 46 patients with the diagnosis of cerebral vascular disease confirmed with imaging study and 138 adult patients without diagnosis of cerebral vascular disease respectively, and that both groups adgested with the criteria of exclusion. Results and conclusions: The most common Cerebral Vascular Disease was the ischemic type. The arterial hypertension, diabetes mellitus type 2 and the harmful consumption of alcohol were risk factors. The consumption of cigarettes, the sedentarism, migraine with aura and dyslipidemia were not or risk factor or protective factor. The Type 2 Diabetes mellitus was the risk factor that most was associated with cerebral vascular disease